Outcomes of intervention treatment for concurrent cardio-cerebral infarction: a case series and meta-analysis - Habib, Mohammed; Elhout, Somaya (Journal of Cardiology and Cardiovascular Medicine, 2023)
Background: The concurrent occurrence of acute ischemic stroke and acute myocardial infarction is an extremely rare emergency condition that can be lethal. The causes, prognosis and optimal treatment in these cases are still unclear. Methods: We conducted the literature review and 2 additional cases at Al-Shifa Hospital, we analyzed clinical presentations, risk factors, type of myocardial infarction, site of stroke, modified ranking scale and treatment options. We compare the mortality rate among patients with combination intervention treatment (both percutaneous coronary intervention for coronary arteries and mechanical thrombectomy for cerebral vessels) and medical treatment at the hospital and 90 days after stroke. Results: In addition to our cases, we identified 94 cases of concurrent cardio-cerebral infarction from case reports and series with a mean age of 62.5 ± 12.6 years. Female 36 patients (38.3%), male 58 patients (61.7%). Only 21 (22.3%) were treated with combination intervention treatment. The mortality rate at hospital discharge was (33.3%) and the mortality rate at 90 days was (49.2%). In patients with the combination intervention treatment group: the hospital mortality rate was 13.3% and the 90-day mortality rate was: 23.5% compared with the mortality rate in medical treatment (23.5% at the hospital and 59.5% at 90 days (p value 0.038 and 0.012 respectively) Conclusion: Concurrent cardio-cerebral infarction prognosis is very poor, about a third of patients died before discharge and half of the patients died 90 days after stroke. Despite only one-quarter of patients being treated by combination intervention treatment, this treatment modality significantly reduces the mortality rate compared to medical treatment.